Designed peptides as nanomolar cross-amyloid inhibitors acting via supramolecular nanofiber co-assembly - Taş, Karin; Volta, Beatrice Dalla; Lindner, Christina; El Bounkari, Omar; Hille, Kathleen; Tian, Yuan; Puig-Bosch, Xènia; Ballmann, Markus; Hornung, Simon; Ortner, Martin; Prem, Sophia; Meier, Laura; et al. (Nature Communications, 2022)
Amyloid self-assembly is linked to numerous devastating cell-degenerative diseases. However, designing inhibitors of this pathogenic process remains a major challenge. Cross-interactions between amyloid-β peptide (Aβ) and islet amyloid polypeptide (IAPP), key polypeptides of Alzheimer’s disease (AD) and type 2 diabetes (T2D), have been suggested to link AD with T2D pathogenesis. Here, we show that constrained peptides designed to mimic the Aβ amyloid core (ACMs) are nanomolar cross-amyloid inhibitors of both IAPP and Aβ42 and effectively suppress reciprocal cross-seeding. Remarkably, ACMs act by co-assembling with IAPP or Aβ42 into amyloid fibril-resembling but non-toxic nanofibers and their highly ordered superstructures. Co-assembled nanofibers exhibit various potentially beneficial features including thermolability, proteolytic degradability, and effective cellular clearance which are reminiscent of labile/reversible functional amyloids. ACMs are thus promising leads for potent anti-amyloid drugs in both T2D and AD while the supramolecular nanofiber co-assemblies should inform the design of novel functional (hetero-)amyloid-based nanomaterials for biomedical/biotechnological applications.
Gesehen am 20.12.2022